2019
DOI: 10.1039/c9ta05444h
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium zwitterions for lighter and chemically-robust MOFs: highly reversible H2S capture and solvent-triggered release

Abstract: The tetrahedral zwitterion of tetrakis(p-carboxyphenyl) phosphonium is employed as a unique building block for robust and lighter MOFs that tolerate sorption of acidic gases including H2S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…1,2 Literature studies detail a broad range of zwitterionic structures as small molecules and as functionalities within macromolecular architectures, including diverse combinations of cations (ammoniums, 3 phosphoniums, 4−6 imidazoliums 7 ) and anions (carboxylates, sulfonates, sulfates, phosphonates, phosphinates, phosphates). 2−11 Investigations of zwitterionic small molecules include their use in metal extraction, 12 self-assembled ionic gels and proton conductivity, 4 catalytic ligands, 6 metal−organic frameworks (MOFs), 13 and interfacial materials for solar cells. 14 Literature examples have demonstrated that phosphonium ions impart improved thermal stability and ion conductivity for both small-molecule and polymeric systems compared to ammonium-based analogues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,2 Literature studies detail a broad range of zwitterionic structures as small molecules and as functionalities within macromolecular architectures, including diverse combinations of cations (ammoniums, 3 phosphoniums, 4−6 imidazoliums 7 ) and anions (carboxylates, sulfonates, sulfates, phosphonates, phosphinates, phosphates). 2−11 Investigations of zwitterionic small molecules include their use in metal extraction, 12 self-assembled ionic gels and proton conductivity, 4 catalytic ligands, 6 metal−organic frameworks (MOFs), 13 and interfacial materials for solar cells. 14 Literature examples have demonstrated that phosphonium ions impart improved thermal stability and ion conductivity for both small-molecule and polymeric systems compared to ammonium-based analogues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[21] The adsorption capacity of Mg-Cuk-1 was 1.41 mmol g-1 at a low concentration of 6 vol % H 2 S and increased to 3.1 mmol g -1 at a high concentration of 15 vol % H 2 S. Mg-Cuk-1 also had a flexible structure, and after five H 2 S adsorption-desorption cycles, the crystallinity still remained, because of the weak interaction between Mg-Cuk-1 framework and H 2 S molecules. Reynolds [22] The latter exhibited exceptionally high chemical stability, allowing complete cycle adsorption with a H 2 S capacity of 8.00 mmol g-1 and triggering the release of H 2 S by solvents such as DMF, H 2 O and MeOH (Figure 3). The high H 2 S adsorption capacity of PCM-75 may be caused by the polarization properties of the frameworks, the presence of charged phosphorus species and highly polarized Mg 3 + nodes.…”
Section: Pore Structuresmentioning
confidence: 99%
“…The use of organophosphine linkers for the preparation of various multifunctional porous coordination polymers dates back to 2008. Since then, a number of materials were designed, especially by Humphrey and co‐workers (phosphine coordination materials, PCMs) . It should be noted they generally comprise carboxylic groups coordinating metal secondary building units (SBUs).…”
Section: Introductionmentioning
confidence: 99%